From the Editor: The Wonder of Science. (September 2021) - Kelly, Rob
Abstract : Just when we thought it was safe to go back in the water, the Delta variant comes along. Its spread has caused ECS to make the 240th Meeting all digital. I was really looking forward to cashing in on some promises of "I'll buy you a beer the next time we get together." My friends should know that compound interest on those continues to accumulate. As we hunker back down, it is appropriate to stop and recognize the almost unimaginable scientific achievement that has led the world away from cataclysm and back toward normality. The speed with which the vaccines have been developed would have been considered science fiction before it actually happened.